RIAU MALAY CULTURE TRANSMISSION AND LEARNING DEVELOPMENT IN THE SOCIETY 5.0 ERA - Kurniady, Dedy; Firman, Firman; Harun, Maizatul Mardiana (Universitas Islam Negeri Sumatera Utara Medan, 2024)
Currently, with the development of technology in the era of society 5.0, society is required to be able to make the best use of technology. Current technological developments have an influence on the development of education and culture, so that education becomes a tool in the process of cultural transmission. The aim of this research is to conduct a theoretical and descriptive study to find out how the transmission of Riau Malay culture and the development of learning in the era of society 5.0 is developing. The appropriate research method to use is a descriptive interview type research method. The results of this research show that technology plays a role in accelerating the process of transmitting Riau Malay culture, as in the Riau Malay proverb